Development of E-Student Worksheets-Based on Guided Inquiry Assisted by Augmented Reality and Three Dimension on Human Excretory System Topic - Isna, Isnanik; Qurrota A'yuna, Wilda; Himmah, Rif'atul (JCER (Journal of Chemistry Education Research), 2023)
21st century places students as an active subjects in the learning process. Electronic Student Worksheets based on guided inquiry and assisted by Augmented Reality (AR) and three-dimensional (3D) technology can facilitate the learning process that can be students centered in the era of rapid technological developments and the pandemic covid-19. The purpose of this research was to produce an electronic student worksheets based on guided inquiry assisted by AR and 3D on valid and practical human excretory system topic to be used in science learning at the VIII grade junior high school level. This study used research and development (R&D) methods with a 4D development model consisting of the stages defining, designing, developing, and disseminating, but in this study, there was no disseminate stage. The electronic student W\worksheets was tested on a limited basis to 32 students of class VIII G SMP Negeri 24 Malang. This study E- Student Worksheet Based on Guided Inquiry Assisted By Augmented Reality and Three Dimension on valid and practical human excretory system material used in science learning at the VIII grade junior high school level. The validity of the developed E- Student Worksheet obtained a percentage of 98.02% with a very valid category. The practicality of the E- Student Worksheet in terms of the assessment process, students obtained a percentage of 97% with a very practical category. Meanwhile, the practicality of E- Student Worksheet in terms of student responses obtained a percentage of 93.25% with a very practical category.